Plan de marketing para la tienda deportiva “Solo Original” en la ciudad Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, para el año 2017 - Ramón Sánchez, Ayda Magale (2017)
This thesis work entitled MARKETING PLAN FOR THE SPORTS SHOP "ONLY ORIGINAL" IN THE NEW CITY LOJA, CANTÓN LAGO AGRIO, PROVINCE OF SUCUMBÍS, FOR THE YEAR 2017, has as general objective Elaborate a Marketing Plan for the company "SOLO ORIGINAL "of the canton Lago Agrio, province of Sucumbíos, which allows determining the commercial objectives to be achieved by detailing strategies and actions that will be carried out to achieve them in a year, it is very reasonable to try to maximize profits and reduce expenses, for It is necessary to improve the planning and organization within the store, with the sole purpose of presenting to the owner a tool that facilitates the control and is a great help for the decision making and a proper administrative management of the same. Also, the present work has had its full theoretical support, which has served to strengthen the information obtained; The methods that were used are: inductive, the same that was used based on the current situation of marketing and its four components (4 Ps), the deductive method, the deductive allowed to design a marketing plan specific to the company SOLO ORIGINAL Of the city of Nueva Loja, the statistical method allowed to tabulate and interpret the survey carried out and the statistical tables; The techniques that were used to collect data are listed below: An interview applied to the Manager of the sports store that determined the strengths and weaknesses, Survey applied to the 337 customers and 6 employees, which allowed the internal analysis of the sports store ; Among the main results was obtained: The weighted total is 2.58, which indicates that the company is not taking advantage of some opportunities and that threats can harm it if it does not potentiate opportunities. According to the EFI matrix obtained, the weighted score of the SOLO ORIGINAL sports store is 2.57, which implies that the store is strong internally. Finally, after having carried out the analyzes, four strategic objectives were determined as a central proposal: To renew the image of the sports shop SOLO ORIGINAL, To promote the company through a Promotions Plan, To select and to make the respective contracts with the means of communication of greater circulation, Tuning and coverage to make known the products offered by the store and Establish permanent training and motivation seminars for all store staff to carry out their activities efficiently. These strategic objectives are designed to promote the activities of marketing, sale and promotion of the services and products offered together with its budget that amounts to the amount of $ 11,073.00; Which is designed to be done within four years. Among the most representative conclusions can be determined that the company does not have promotions, an advertising plan, training programs for staff and does not make a new image of your store.